Study of digital discourse in the Algerian sociolinguistic context - Noura, Aoudia (Journal of Ecohumanism, 2026)
This work falls within the field of sociolinguistics and aims to analyze the linguistic practices of young Algerians on social media, particularly Facebook. Using a corpus of posts and comments collected on this platform, the study will examine code-switching, understood as the shift from one linguistic system to another within the same discursive exchange. The research will identify the forms this resource takes, the varieties involved, and the functions it fulfills in technology-mediated communication. Furthermore, the characteristics of digital discourse will be analyzed to understand how users mobilize their linguistic repertoires in this environment. In this way, the study seeks to contribute to a better understanding of the communicative behaviors of Algerian internet users by promoting the creation and dissemination of expressive mechanisms specific to online interaction.